Conspiracy Theories, Vaccine Hesitancy and Determinants of Vaccination Acceptance in Nigeria: A Conceptual Review - Yusuf, Adekunle; Ogwezzy-Ndisika, Abigail O.; Ibraheem, Ismail A.; Suraj, Olunifesi A. (Journal of Communication, 2024)
Purpose: This conceptual review aims to dissect the intricate web of conspiracy theories, vaccine hesitancy and determinants of vaccination acceptance within Nigeria's socio-cultural context, shedding light on their genesis, propagation and impact on public health outcomes. Methodology: Employing a multidisciplinary approach, this study synthesizes existing literature and theoretical frameworks from various disciplines, including sociology, anthropology, public health, and communication studies. Methodological rigor is ensured through comprehensive literature review and critical appraisal of relevant studies, enabling a holistic exploration of the subject matter. Findings: Through a systematic analysis, the review identifies and examines socio-cultural, economic and political influences that shape vaccination behavior in Nigeria. It illuminates the multifaceted determinants contributing to vaccine hesitancy, ranging from religious beliefs to historical legacies to socio-economic factors and healthcare accessibility challenges. The review also highlights the genesis and propagation of conspiracy narratives, their impact on public trust in vaccination and consequent implications for immunization uptake. Unique Contribution to Theory, Policy and Practice: This review makes several contributions to theory, policy, and practice in the field of vaccination and public health. Firstly, it advances theoretical understanding by synthesizing existing knowledge and proposing conceptual frameworks that elucidate the socio-cultural, economic, and political determinants of vaccination behavior in Nigeria. Secondly, it informs policy development by identifying key areas for intervention, such as addressing vaccine hesitancy, countering misinformation, and strengthening healthcare infrastructure to enhance vaccine delivery. Finally, it offers practical insights for public health practitioners and policymakers, providing evidence-based recommendations for designing effective vaccination campaigns, communication strategies, and community engagement initiatives tailored to the Nigerian context.